Novel Urinary Glycan Biomarkers Predict Cardiovascular Events in Patients With Type 2 Diabetes: A Multicenter Prospective Study With 5-Year Follow Up (U-CARE Study 2) - Mise, Koki; Imamura, Mariko; Yamaguchi, Satoshi; Watanabe, Mayu; Higuchi, Chigusa; Katayama, Akihiro; Miyamoto, Satoshi; Uchida, Haruhito A.; Nakatsuka, Atsuko; Eguchi, Jun; Hida, Kazuyuki; Nakato, Tatsuaki; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Although various biomarkers predict cardiovascular event (CVE) in patients with diabetes, the relationship of urinary glycan profile with CVE in patients with diabetes remains unclear. Methods: Among 680 patients with type 2 diabetes, we examined the baseline urinary glycan signals binding to 45 lectins with different specificities. Primary outcome was defined as CVE including cardiovascular disease, stroke, and peripheral arterial disease. Results: During approximately 5-year follow-up period, 62 patients reached the endpoint. Cox proportional hazards analysis revealed that urinary glycan signals binding to two lectins were significantly associated with the outcome after adjustment for known indicators of CVE and for false discovery rate, as well as increased model fitness. Hazard ratios for these lectins (+1 SD for the glycan index) were: UDA (recognizing glycan: mixture of Man5 to Man9): 1.78 (95% CI: 1.24-2.55, P=0.002) and Calsepa (High-Man [Man2-6]): 1.56 (1.19-2.04, P=0.001). Common glycan binding to these lectins was high-mannose type of N-glycans. Moreover, adding glycan index for UDA to a model including known confounders improved the outcome prediction (Difference of Harrel’s C-index: 0.028 [95% CI: 0.001-0.055, P=0.044], net reclassification improvement at 5-year risk increased by 0.368 [0.045-0.692, P=0.026], and the Akaike information criterion and Bayesian information criterion decreased from 725.7 to 716.5, and 761.8 to 757.2, respectively). Conclusion: The urinary excretion of high-mannose glycan may be a valuable marker for predicting CVE in patients with type 2 diabetes, which provide the rationale to explore the mechanism underlying abnormal N-glycosylation in CVE of patients with diabetes.